Molecular dynamics of polysiloxane polar-nonpolar co-networks and blends studied by dielectric relaxation spectroscopy. (1st August 2018) - Asandulesa, Mihai; Musteata, Valentina Elena; Bele, Adrian; Dascalu, Mihaela; Bronnikov, Sergei; Racles, Carmen
Abstract: Polar-nonpolar silicone materials of different morphology and composition were investigated by means of broadband dielectric relaxation spectroscopy in order to elucidate the effect of polar content and nature of the interface on the segmental mobility of polydimethylsiloxane (PDMS) chains. The variation of dielectric parameters with temperature revealed two distinct α-relaxations corresponding to dynamic glass transitions of the components, while another polarization phenomenon was evidenced due to accumulations of charges at the interphases between the two polymers with different electrical properties. It was found that the secondary β-relaxation was favored by the increased content of polar groups, while this parameter had the reverse influence on both αPDMS and αP62, restricting the PDMS chain segment mobility. The activation energy of the interfacial polarization decreased with the polarity, showing increased mobility of charge carriers and less restriction to the interfacial polarization. Graphical abstract: Image 1 Highlights: Polysiloxane polar-nonpolar co-networks and blends studied by BDS. Polar domains restrict the PDMS chain segment mobility. The segmental movements of the polar copolymer are facilitated by the PDMS. Addition of polar copolymer allows less restriction to the interfacial polarization.